Analysis of The Day of The Week Effect On Virtual Currency Returns On The Cryptocurrency Market - Tantober, Basthian; Syahputra Silalahi, Amlys; Syahyunan; Marlina, Lisa (TALENTA Publisher, Universitas Sumatera Utara, 2021)
The purpose of this study was to determine and analyze the influence of the day of the week effect on virtual currency return at cryptocurrency market. This research was an empirical study on trading day and virtual currency returns. This research was taking 26 cryptocurrencies that listed during January,1st 2018 until December, 31st 2018 and used daily return of each virtual currencies. The analytical method used is descriptive analysis method and multiple linear regression analysis method with dummy variables. This type of research is associative research and the data used are secondary data that has been processed and published. Data is processed statistically with the EViews program, namely the t test model and f test. The results of this study indicate that simultaneously the trading days have a significant effect on virtual currency return. Partially, trading day variables of Tuesday, Thursday, and Friday have a positive and significant effect on virtual currency return